The use of masks in sport: an integrative review during Covid-19 - Prieto Andreu, J. M. (Cultura, Ciencia y Deporte, 2021)
The use of the mask in the sports field has been studied to improve the athlete's performance and its protection against a contaminated environment, such as the one existing in the current pandemic panorama of Covid-19. This review analyzes the impact of the mask on different physiological factors while doing physical exercise. A random selection was made of 2,420 studies published in Scholar Google, 118 in SCOPUS and 137 studies published in WOS between the periods 2016-2020, with 95% confidence and +/- 4.3 sampling error, which served for the selection and final analysis of 10 studies chosen intentionally following CTFPHC levels of evidence and the methodological rigor of a structured classification system called PEDro Scale. The results highlight that the use of masks in athletes causes hypoxic and hypercapnic breathing at a certain intensity; the use of masks such as the Elevation Training Mask (ETM) trains the respiratory muscles but does not improve lactic anaerobic performance as intermittent hypoxic training (IHT) does in height. It is discussed about hypoxia and hypercapnia conditions and the use of masks to improve physical performance in athletes.